Re-entrant limits of stability of the liquid phase and the Speedy scenario in colloidal model systems - Rovigatti, L; Bianco, V; Tavares, J; Sciortino, F (AIP Publishing, 2017)
A re-entrant gas-liquid spinodal was proposed as a possible explanation of the apparent divergence of the compressibility and specific heat off supercooling water. Such a counter-intuitive possibility, e.g., a liquid that becomes unstable to gas-like fluctuations on cooling at positive pressure, has never been observed, neither in real substances nor in off-lattice simulations. More recently, such a re-entrant scenario has been dismissed on the premise that the re-entrant spinodal would collide with the gas-liquid coexisting curve (binodal) in the pressure-temperature plane. Here we study, numerically and analytically, two previously introduced one-component patchy particle models that both show (i) a re-entrant limit of stability of the liquid phase and (ii) a re-entrant binodal, providing a neat in silico (and in charta) realization of such unconventional thermodynamic scenario.